Perplexing Role of P-Glycoprotein in Tumor Microenvironment - Robinson, Kianna; Tiriveedhi, Venkataswarup (Frontiers in Oncology, 2020)
Development of multidrug resistance (MDR) still remains a major obstacle to the long-term success of cancer therapy. P-glycoprotein (P-gp) is a well-identified membrane transporter with capability to efflux drug molecules out of the cancer cell leading to reduced efficiency of chemotherapy. Cancer cells upregulate P-gp expression as an adaptive response to evade chemotherapy mediated cell death. While several P-gp inhibitors have been discovered by in silico and pre-clinical studies, very few have successfully passed all phases of the clinical trials. Studies show that application of P-gp inhibitors in cancer therapy regimen following development of MDR achieved limited beneficial outcomes. While, the non-specific substrate binding to P-gp has made the drug-design a challenge, a bigger perplexing challenge comes from its role in tumor immunology. Expression of P-gp was noted immune cell phenotypes with apparently antagonistic functionality. Both pro-tumor MΦ2-macrophages and, anti-tumor NK-cell and Th17/CD4+T cell subsets have shown enhanced expression of P-gp. While drug based inhibition of P-gp in pro-tumor immune cell phenotypes could promote tumor elimination, however, it would not be a rational choice to exert inhibition of P-gp on anti-tumor immune cell phenotypes. This mutually exclusive paradigm of P-gp functionality requires a more comprehensive and detailed understanding of its role in tumor microenvironment with active interplay of cancer and immune cells in the tumor mileu. In this review, we focus on the current understanding of the role of P-gp in cancer cells and immune cells and finally attempt to highlight some caveats in the current understanding of its role in comprehensive tumor microenvironment along with challenges in the development of P-gp inhibitors towards anti-cancer therapy.